MAPPING ENGLISH IN THE LINGUISTIC LANDSCAPE OF KAMPUNG INGGRIS PARE: A CASE OF ENTERPRISE SIGNS - Hurrotul Firdausiyah (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
Since Pare is known as Kampung Inggris, English progressively impacts the language community and the linguistic landscape. This article tries to describe the use of English on enterprise signs in the linguistic landscape of Kampung Inggris Pare and the underlying motivations for using English on those signs. I collected the data by using observation and photograph methods. I walked through some strategic streets in Kampung Inggris Pare, then observed, and photographed the enterprise signs. The findings indicate that English is mainly used on enterprise signs in Kampung Inggris Pare, either on English education enterprises or other enterprises (non-English education enterprise signs). However, a higher number of English is used by other enterprises (non-English education enterprises). Furthermore, English is used on those enterprise signs monolingually, bilingually, and multilingually. The dominance of English appears in bilingual signs in Indonesian language. Besides that, English in bilingual text also appears in other languages (Javanese, Korean, Japanese, Dutch, and Arabic). The research findings also reveal that English on the enterprise signs not only shows the modernity, the success, and the internationalness orientations but also emphasizes the identity of Pare as Kampung Inggris. Nevertheless, there is resistance to English by the local society in this linguistic landscape of Kampung Inggris Pare to maintain the local language, Javanese, amidst the increasing number of people using English in that area.